Diversity of SCAR Markers of Pyricularia grisea Isolated from Digitaria ciliaris Following Cross Infection to Rice - SRI LISTIYOWATI; UTUT WIDYASTUTI; GAYUH RAHAYU; ALEX HARTANA; MUHAMMAD JUSUF (Microbiology Indonesia, 2011)
Cross infection of Pyricularia grisea from grass to rice and vice versa has been reported, but genetic changes are not known yet. This research aimed at estimating the possibility of the genotype alteration in P. grisea dc4 isolated from Digitaria ciliaris, following cross infection to either rice cv. Kencana bali, Cisokan, and IR64 or Panicum repens, Cynodon dactylon, Digitaria sp., and Ottochloa nodosa. The genotypes were analyzed by employing three SCAR markers, Cut1; PWL2; and Erg2. The results indicated that the dc4 was only able to infect Kencana bali, Cisokan, and P. repens. The dc4 had only two out of three SCAR markers, Cut1 and Erg2. Host shift was followed by genotype alteration in two loci of SCAR. Isolates derived from lesions on Kencana bali (dc4-kb) and Cisokan (dc4-c) of the dc4 infection, both lost their Cut1 and gained PWL2. On the contrary, there was no genotype alteration from dc4 to isolate derived from P. repens of dc4 infection (dc4-pr). Neither the isolate dc4-kb that was cross-inoculated to Cisokan nor the dc4-c that was cross-inoculated to Kencana bali showed SCAR marker change. In comparison, race 173 isolate and those derived from Kencana bali and Cisokan did not show genotype alteration. All had two out of three SCAR markers, PWL2 and Erg2. The isolate 173 was adapted to rice. This indicated that genotype diversity of the dc4 might arise following host shift from grass to rice.Pyricularia grisea merupakan cendawan blas yang telah diketahui memiliki kisaran inang luas selain pada padi. Infeksi silang cendawan blas pada rumput ke padi dan sebaliknya telah dilaporkan, tetapi perubahan genetiknya belum dilaporkan. Tujuan penelitian ini menganalisis kemampuan infeksi silang dan perubahan genotipe P. grisea dc4 asal Digitaria ciliaris dalam perpindahannya ke padi cv. Kencana bali, Cisokan, dan IR64 atau rumput Panicum repens, Cynodon dactylon, Digitaria sp. dan Ottochloa nodosa. Genotipe P. grisea dianalisis melalui tiga marka SCAR, yaitu Cut1; PWL2; dan Erg2. Isolat dc4 memiliki 2 marka SCAR, yaitu Cut1 dan Erg2; tidak memiliki PWL2. Isolat dc4 hanya mampu menginfeksi silang Kencana bali, Cisokan, dan P. repens. Turunan isolat dc4 sebagai hasil infeksi silang ke Kencana bali (dc4-kb) dan Cisokan (dc4-c) menunjukkan perubahan genotipenya, yaitu Cut1 tidak teramplifikasi pada keduanya; PWL2 teramplifikasi;, serta Erg2 tetap teramplifikasi. Sebaliknya, turunan isolat dc4 sebagai hasil infeksi silang ke P. repens (dc4-pr) tidak mengalami perubahan genotipe. Turunan isolat dc4-kb sebagai hasil infeksi silang ke Cisokan, maupun turunan isolat dc4-c dari Kencana bali, juga tidak menunjukkan perubahan genotipe, yaitu tetap menunjukkan keberadaan PWL2 dan Erg2. Sebagai pembanding digunakan isolat ras 173 yang diisolasi dari padi. Genotipe isolat tersebut maupun turunannya, sebagai hasil infeksi silang ke Kencana bali dan Cisokan, tidak menunjukkan perubahan. Perubahan genotipe dc4 terjadi mengikuti pergantian inang dari rumput ke padi.